Holocene displacement field at an emerged oceanic transform-ridge junction: The Husavik-Flatey Fault – Gudfinnugja Fault system, North Iceland. (June 2015) - Pasquarè Mariotto, F.; Bonali, F.L.; Tibaldi, A.; Rust, D.; Oppizzi, P.; Cavallo, A.
Abstract: Our research focuses on Holocene tectonics in a broad area surrounding the junction between the active NW–SE trending Husavik-Flatey transform fault (HFF) and the N–S Gudfinnugja normal fault (GF), an exceptional example of onshore transform-ridge intersection. We mapped 637 minor and major faults, and measured the dip-slip and strike-slip offset components on the major faults. We also mapped 1016 individual tension fractures, as well as opening directions on the most reliable ones. The results indicate that this portion of the HFF comprises major right-stepping segments, with both normal and right-lateral strike-slip components, linked by local normal faults. The entire GF always shows pure dip-slip normal displacements, with a strong decrease in offset at the junction with the HFF. Fissure opening directions are in the range N45°-65°E along the HFF, N90°E along the GF, and N110°E within the area south of the HFF and west of the GF. Fault kinematics and fissure openings suggest a displacement field in good agreement with most of present-day GPS measurements, although our data indicate the possible long-term Holocene effects of the superimposition of magma-related stresses on the regional tectonic stresses. The HFF and the GF work together as a structural system able to accommodate differential crustal block motion, and possibly past dyke intrusions. Highlights: We reconstructed the Holocene kinematics at a ridge-transform junction. We determined offset components at the Husavik-Flatey Fault and Gudfinnugja Fault. We mapped 1016 tension fractures and measured the most reliable opening directions. Displacements resulted from the influence of magma stresses and tectonic stresses. Previous substrate structures influenced the development of the Husavik-Flatey Fault.